2002
DOI: 10.1353/rhe.2002.0018
|View full text |Cite
|
Sign up to set email alerts
|

20th Century Postsecondary Practices and Policies to Control Gay Students

Abstract: This paper traces three forms of control taken by postsecondary regulations of the sexual mores of gay male college students, through institutional responses to particular acts: expulsion of those found, or believed, to engage in homosexual activity; the implementation of undercover "sting" operations; and the attempted prevention of student organizing. Despite changes in these patterns since the 1950s, respondents still comment on how these practices influenced both their activities and their sense of identit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…Yet they and their colleagues in the growing field of college counseling sometimes took a treatment approach rather than a disciplinary approach. Believing that homosexuality was a treatable disease, not an untreatable personality disorder, well-meaning student affairs professionals might be convinced by campus medical staff to keep a student on campus and enlist him or her in psychological treatment (Bailey, 2002;Dilley, 2002aDilley, , 2002b. Rooted in counseling psychology, this approach followed standard practice at a time when homosexuality was listed as a disease in the American Psychiatric Association's Diagnostic and Statistical Manual of Mental Disorders (1968).…”
Section: Homosexuality As Deviance and Disease: Research Prior To 1974mentioning
confidence: 99%
See 1 more Smart Citation
“…Yet they and their colleagues in the growing field of college counseling sometimes took a treatment approach rather than a disciplinary approach. Believing that homosexuality was a treatable disease, not an untreatable personality disorder, well-meaning student affairs professionals might be convinced by campus medical staff to keep a student on campus and enlist him or her in psychological treatment (Bailey, 2002;Dilley, 2002aDilley, , 2002b. Rooted in counseling psychology, this approach followed standard practice at a time when homosexuality was listed as a disease in the American Psychiatric Association's Diagnostic and Statistical Manual of Mental Disorders (1968).…”
Section: Homosexuality As Deviance and Disease: Research Prior To 1974mentioning
confidence: 99%
“…The 1969 Stonewall Riots, led by working-class drag queens of color in reaction to persistent harassment by New York City police officers, sparked a movement on college campuses and in urban enclaves of gays and lesbians (see D'Emilio, 1992). The first known gay student organization-the Student Homophile League at Columbia University-was founded immediately after the riots, in the same city (Dilley, 2002a). Five years after the American Psychiatric Association reversed its stance on homosexuality, the New York Times Magazine reported there were more than 200 campus gay and lesbian groups (Hechinger & Hechinger, 1978), some of which were compelled to mount legal challenges against their institutions in order to be recognized (Stanley, 1983(Stanley, -1984.…”
Section: Homosexuality As Deviance and Disease: Research Prior To 1974mentioning
confidence: 99%
“…The modern gay rights movement, too, has come to the campus and university. Although students on campus once had to live clandestine lives in fear of discovery, shame, and expulsion (Dilley, 2002), students today are coming out at earlier and earlier ages (Broido, 2004). Additionally, several studies have indicated that, compared to decades past, U.S. college students have more positive attitudes toward their gay, lesbian, bisexual, and transgender peers than ever before (e.g., Altemeyer, 2001, Avery et al, 2007, and Newman, 2007.…”
Section: Resource Mobilization and Political Opportunitymentioning
confidence: 99%
“…More than 2,000 campuses have LGBT student groups (Dilley, 2002), and more than 150 campuses have professionally staffed LGBT Resource Centers (Consortium of Higher Education LGBT Resource Professionals, 2009). Faculty have been a part of many of these changes through their work on faculty senates and university committees, serving as LGBT student group advisors, and participating in individual advocacy, informal outreach, organizing, protests, and lawsuits (Bilimoria & Stewart, 2009;Taylor & Raeburn, 1995).…”
Section: Review Of Literaturementioning
confidence: 99%